Revision and phylogenetic analysis of the spider genus Glenognatha Simon, 1887 (Araneae, Tetragnathidae) - Cabra García, Jimmy Jair (2013)
A taxonomic revision and phylogenetic analysis of the spider genus Glenognatha Simon, 1887 is presented. The analysis is based on a data set including 24 Glenognatha species plus eight outgroup representatives of three additional tetragnathine genera and one metaine, scored for 82 morphological characters. Eight unambiguous synapomorphies support the monophyly of Glenognatha, all free of homoplasy. Some internal clades within the genus are well-supported and its relationships are discussed. The genus Glenognatha has a broad distribution occupying the Neartic, Neotropic, Afrotropic, Indo-Malaya and Oceania ecozones. As revised here, Glenognatha comprises 27 species, four of them only know from males. New morphological data are provided for the description of thirteen previously described species. Eleven species are newly described: G. sp. nov. 1, G. sp. nov. 3, G. sp. nov. 4 and G. sp. nov. 7 from southeast Brazil, G. sp. nov. 6, G. sp. nov. 9 and G. sp. nov. 10 from the Amazonian region, G. sp. nov. 2, G. sp. nov. 5 and G. sp. nov. 8 from northern Andes and G. sp. nov. 11 from central Mexico and Southern United States. Females of G. minuta Banks, 1898, G. gaujoni Simon, 1895 and G. gloriae (Petrunkevitch, 1930) and males of G. globosa (Petrunkevitch, 1925) and G. hirsutissima (Berland, 1935) are described for the first time. Three new combinations are proposed in congruence with the phylogenetic results: G. argyrostilba (O. P.-Cambridge, 1876), G. dentata (Zhu & Wen, 1978) and G. tangi (Zhu, Song & Zhang, 2003), all previously included in Dyschiriognatha. The following taxa are newly synonymized: Dyschiriognatha montana Simon, 1897, Glenognatha mira Bryant, 1945 and Glenognatha maelfaiti Baert, 1987 with Glenognatha argyrostilba (O. P.-Cambridge, 1876) and Glenognatha centralis Chamberlin, 1925 with Glenognatha minuta Banks, 1898. A key to species of Glenognatha and distribution maps are provided.